The ankle ([St. Louis, MO] : Mosby-Year Book, 1996)
This exciting video series discusses and demonstrates proper taping and wrapping procedures. Each video includes the taping or wrapping procedures purpose, correct anatomical position and proper supply selection.To complete your medicine library, look for the following videos in this series on the ankle, the foot and lower leg, knee,shoulder and elbow, the wrist and hand.
Keywords: Ankle Injuries -- therapy -- videocassettes; Athletic Injuries -- therapy -- videocassettes; Bandages -- videocassettes